Interfacial effects in nano-silica/polypropylene composites fabricated by in-situ chemical blowing (eXPRESS Polymer Letters)
By mixing macromolecular blowing agent grafted nano-SiO2 with polypropylene (PP) melt, the nanoparticle agglomerates can be pulled apart due to the in-situ bubble-stretching resulting from gasification of the side foaming groups on the grafted polymer. The present work evaluated the interfacial effect in the PP based nanocomposites prepared using the aforesaid technique through introducing rubbery components to the backbone of the grafted polymer chains. The results indicated that deagglomeration of the nanoparticles was not bound to yield the highest properties of the composites. The positive effect of the nanoparticles was brought into full play because of the joint contributions of particles dispersion status and interfacial interaction. An interlayer with proper flexibility ensured an overall enhancement of mechanical properties, especially impact strength, of the nanocomposites.